'A record of abortive enquiries and empty of achievement?': the White Fish Authority, 1951–1981. (2nd July 2020) - Wilcox, Martin
ABSTRACT: The White Fish Authority was the government development body for most of the British fishing industry from its establishment in 1951 until its merger with the Herring Industry Board thirty years later. Setting the WFA in the context of wider debates over the efficacy of development councils in general, this article surveys and critiques the record of the Authority. It argues that despite weaknesses in its conception, financing and management, the Authority was nevertheless a positive force overall.